Analysis of the Role of Communities in Social Community Development in Kefamenanu City, Timor Tengah Utara District - Andre Pattipeilohy; Surya Yudha Regif; Marisa Susanty Bette Seran (East Asian Journal of Multidisciplinary Research, 2023)
This research aims to explain the role of the community in social community development in Kefamenanu City, North Central Timor District. The method in the research uses descriptive qualitative to explain the phenomena that occur. Data collection techniques through primary data in-depth interviews and secondary data by referring to journals, books, and online media. Data analysis techniques used in the research through data reduction, data presentation, and conclusion. This finding shows that Karang Taruna is a youth organization that plays a role in various social activities and development programs in Indonesia. Karang Taruna is involved in several community development projects based on invitations from local governments at both the sub-district and village levels, such as tourism development, social activities during the past COVID-19 pandemic, and social conflict resolution. Nevertheless, the role of Youth Organizations in Kefamenanu City still needs more resources as initiators or initiators of the movement, so the role of Karang Taruna has yet to be seen as the spearhead of superior generational change.